2015
DOI: 10.1097/dcr.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index Predicts Severe Complications, Recurrence, and Poor Prognosis in Patients With Colorectal Cancer Undergoing Primary Tumor Resection

Abstract: The preoperative prognostic nutritional index predicts severe complications, recurrence, and poor prognosis in patients with colorectal cancer who are undergoing primary tumor resection. Investigation of the nutritional and immunologic statuses using the prognostic nutritional index could be a useful clinical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
181
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(197 citation statements)
references
References 25 publications
6
181
0
10
Order By: Relevance
“…The observation was supported by previous studies which indicated that poor nutritional status was significantly parallel to tumor progression [30]. Tokunaga et al recently demonstrated in a cohort of 556 patients with colorectal cancer undergoing surgery that poor nutritional status was correlated with tumors invading muscular or deeper layers, distant metastasis, tumor recurrence, and poor survival [31].…”
Section: Discussionsupporting
confidence: 54%
“…The observation was supported by previous studies which indicated that poor nutritional status was significantly parallel to tumor progression [30]. Tokunaga et al recently demonstrated in a cohort of 556 patients with colorectal cancer undergoing surgery that poor nutritional status was correlated with tumors invading muscular or deeper layers, distant metastasis, tumor recurrence, and poor survival [31].…”
Section: Discussionsupporting
confidence: 54%
“…[9,10,35] Further, we linked decreased PNI to increased risk of hematogenous metastasis but not peritoneal dissemination. A reasonable explanation for these findings is that immunocompetence and nutritional status are more relevant to hematogenous metastasis of circulating tumor cells because of the effects of compromised tumor immunity associated with the types and levels of circulating cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Since the concept of a prognostic nutrition index (PNI) was 1st suggested in 1980, various PNIs were considered as integral parameters that can reflect immunocompetence and nutritional status with greater accuracy compared with that of a single variable. [810] Onodera's PNI (10 × albumin g/dL) + (0.005 × lymphocyte count/mm 3 ) is associated with outcomes of patients with different malignancies. [9,1113] Advanced GC causes debilitating malnutrition and deterioration of the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with colorectal cancer and a low PNI have a poor prognosis [26]. A PNI of less than the COV of 45.5 has been reported to be an independent risk factor for serious complications, such as myocardial infarction and pulmonary embolism [27]. …”
Section: Discussionmentioning
confidence: 99%